2016
DOI: 10.1016/j.cbi.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

C5 induces different cell death pathways in promastigotes of Leishmania amazonensis

Abstract: Leishmaniasis is a neglected infection that is caused by Leishmania protozoa, affecting millions of people worldwide, mainly in tropical and subtropical regions. This disease has different clinical forms: cutaneous, mucocutaneous, and visceral. The drugs that are currently available for the treatment of this infection have limitations, such as high toxicity, long-term treatment, and leads to drug-resistant strains. Numerous studies, in various experimental models, have sought to develop more effective and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
(35 reference statements)
0
9
0
2
Order By: Relevance
“…The β-carboline nucleus was prepared from commercial L-tryptophan (1) according to the methodology described by our research group. [14][15][16][17][18][19] The L-tryptophan methyl ester (2) was subjected to the condensation reaction of Pictet-Spengler with different aldehydes in acid medium, providing the methyl 1-(substituted-phenyl)-1,2,3,4-tetrahydro-9H-β-carboline-3-carboxylates 3a-3i, which were oxidized with sulfur under reflux in xylene to the methyl 1-(substituted-phenyl)-9H-β-carboline-3-carboxylates 4a-4i. The basic hydrolysis reaction of 4a-4i provided the 1-(substituted-phenyl)-9H-β-carboline-3-carboxylic acids 5a-5i.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The β-carboline nucleus was prepared from commercial L-tryptophan (1) according to the methodology described by our research group. [14][15][16][17][18][19] The L-tryptophan methyl ester (2) was subjected to the condensation reaction of Pictet-Spengler with different aldehydes in acid medium, providing the methyl 1-(substituted-phenyl)-1,2,3,4-tetrahydro-9H-β-carboline-3-carboxylates 3a-3i, which were oxidized with sulfur under reflux in xylene to the methyl 1-(substituted-phenyl)-9H-β-carboline-3-carboxylates 4a-4i. The basic hydrolysis reaction of 4a-4i provided the 1-(substituted-phenyl)-9H-β-carboline-3-carboxylic acids 5a-5i.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, our research group has already demonstrated the antileishmanial activity of β-carbolines containing substituents at 1-and 3-positions of the β-carboline nucleus. [14][15][16][17][18][19][20] In the works developed by Tonin et al 16 and Pedroso et al, 17 it was demonstrated the activity of N -alkyl-(1-phenylsubstitutedβ-carboline)-3-carboxamides against promastigote, axenic amastigote and intracellular amastigote forms of Leishmania amazonensis. The compound with the N-benzyl-carboxamide group at C-3 was active against promastigote and axenic amastigote forms with IC 50 (50% inhibitory concentration) values of 2.6 and 1.0 µM, respectively, 17 and killed L. amazonensis promastigotes through different cell death pathways, including apoptosis and autophagy.…”
Section: Synthesis Antileishmanial Activity and Spin Labeling Epr Stmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) perda do potencial mitocondrial; (4) modificações no ciclo celular e (5) liberação do citocromo C. Além dessas alterações moleculares, mudanças morfológicas típicas do processo apoptótico também são vistas em tripanosomatídeos, a saber: condensação da cromatina, fragmentação do DNA, encolhimento celular, formação de corpos apoptóticos e formação de blebbing na membrana plasmática (DEBRABANT et al, 2003;DUSZENKO et al, 2006;MENDES et al, 2016;MENNA-BARRETO, 2019). A tabela 1 mostra a comparação de fenótipos apoptóticos presentes em organismos multicelulares e tripanosomatídeos.…”
Section: Sumáriounclassified